THE VARIABILITY OF ADOLESCENTS' INTERESTS IN THE ACADEMIC CONTEXT - Claudia Sălceanu (National Centre for Policy and Evaluation in Education, 2019)
Adolescence is among the most studied developmental stages. It represents critical transition stage in human development, characterized by a large amount of changes, to which young people must find creative solutions in order to adapt. Among the most important developmental tasks is the dimension of motivation and, in particular, interests as motivational structures. A convenience sample of 1360 adolescents, aged between 12 and 24 years old, filled in the Questionnaire for Evaluation of Vocational Interests (Cognitrom Assessment System). The objectives and hypotheses of the research are mainly focused on the identification of the existing differences in the area of interests, based on the following criteria: age, gender and environment of provenance. The study identifies a preference of the postadolescents for the social and investigative interests; a preference for artistic, social and realistic interests of girls; and a preference of urban-based adolescents for conventional and investigative interests. Results highlight the importance of identifying the variability of interests for both a better knowledge of this developmental stage and a better organization of the instructive-educational activities, thus supporting the development of career counseling and guidance in schools, high-schools and universities.